Healthy city: global systematic scoping review of city initiatives to improve health with policy recommendations - Shaun Danielli; Hutan Ashrafian; Ara Darzi (BMC, 2023)
Abstract Background Global health will increasingly be determined by cities. Currently over half of the world's population, over 4 billion people, live in cities. This systematic scoping review has been conducted to understand what cities are doing to improve health and healthcare for their populations. Methods We conducted a systematic search to identify literature on city-wide initiatives to improve health. The study was conducted in accordance with PRISMA and the protocol was registered with PROSPERO (CRD42020166210). Results The search identified 42,137 original citations, yielding 1,614 papers across 227 cities meeting the inclusion criteria. The results show that the majority of initiatives were targeted at non-communicable diseases. City health departments are making an increasing contribution; however the role of mayors appears to be limited. Conclusion The collective body of evidence identified in this review, built up over the last 130 years, has hitherto been poorly documented and characterised. Cities are a meta-system with population health dictated by multiple interactions and multidirectional feedback loops. Improving health in cities requires multiple actions, by multiple actors, at every level. The authors use the term 'The Vital 5'. They are the five most important health risk factors; tobacco use; harmful alcohol use; physical-inactivity, unhealthy diet and planetary health. These 'Vital 5' are most concentrated in deprived areas and show the greatest increase in low and middle income countries. Every city should develop a comprehensive strategy and action plan to address these 'Vital 5'.